Sosialisasi Budaya Cuci Tangan Guna Meningkatkan Perilaku Hidup Sehat pada Anak PAUD NEKFONIS Kabupaten Kupang - Su, Delfridus Hendriko; Pally, Keren Y; Indriyati, Indriyati; Kaha, Hendrikus Likusina; Lawalu, Stephanie Perdana Ayu (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
This community service is based on the results of observations by the Implementation Team, which concluded that most NEKFONIS PAUD students are not accustomed to washing their hands after activities, the school lacks a designated handwashing area, and teachers have not instilled this habit in PAUD students. This program aims to promote PHBS (Clean Living Behavior) in early childhood. The program consists of 35 early childhood children, divided into two groups: Group A, comprising 22 children aged 3-5 years, and Group B, comprising 13 children aged 5-6 years. There are also 35 parents of students and two educators. The methods used to implement this service include observation, interviews, socialization, and direct practice on the importance of clean and healthy living behaviors. The results of this community service include changes in clean and healthy living behaviors in early childhood and among parents, as well as educators realizing the importance of implementing clean and healthy living behaviors at the Nekfonis Paud school in South Amarasi District, Kupang Regency.